2018
DOI: 10.1038/s41437-018-0089-7
|View full text |Cite
|
Sign up to set email alerts
|

Out of Africa: demographic and colonization history of the Algerian mouse (Mus spretus Lataste)

Abstract: North Africa is now recognized as a major area for the emergence and dispersal of anatomically modern humans from at least 315 kya. The Mediterranean Basin is thus particularly suited to study the role of climate versus human-mediated changes on the evolutionary history of species. The Algerian mouse (Mus spretus Lataste) is an endemic species from this basin, with its distribution restricted to North Africa (from Libya to Morocco), Iberian Peninsula and South of France. A rich paleontological record of M. spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 87 publications
1
2
0
Order By: Relevance
“…This result is consistent with the continuous presence of this species over the EH2 sequence, with no significant changes in terms of abundance over time (Stoetzel et al 2011) and a stability in morphology and size of molars from the Late Pleistocene to the Middle Holocene (Stoetzel et al 2013). This result may be related to a strong adaptability of this generalist species to environmental changes and/or a continuous presence of suitable habitats for this species in the Rabat-Temara region through the Late Quaternary (Lalis et al 2019). Geometric morphometric analysis of Meriones molars has shown that during the Late Pleistocene, both M. shawii and M. grandis were present in western Morocco (Stoetzel et al 2017).…”
Section: Phenotypic Variations Under Changing Environmentssupporting
confidence: 84%
“…This result is consistent with the continuous presence of this species over the EH2 sequence, with no significant changes in terms of abundance over time (Stoetzel et al 2011) and a stability in morphology and size of molars from the Late Pleistocene to the Middle Holocene (Stoetzel et al 2013). This result may be related to a strong adaptability of this generalist species to environmental changes and/or a continuous presence of suitable habitats for this species in the Rabat-Temara region through the Late Quaternary (Lalis et al 2019). Geometric morphometric analysis of Meriones molars has shown that during the Late Pleistocene, both M. shawii and M. grandis were present in western Morocco (Stoetzel et al 2017).…”
Section: Phenotypic Variations Under Changing Environmentssupporting
confidence: 84%
“…The timing of the first contact of M. spretus and M. m. domesticus is not precisely known. Mus spretus likely colonized Europe first from Northern Africa via the Gibraltar strait sometime during the last 10,000 years ( Lalis et al 2019 ). Cucchi et al (2020) estimate that M. m. domesticus expanded their range westward to Europe from an ancestral population in the Iranian Plateau after the Bronze Age (∼4,000 years ago).…”
Section: Discussionmentioning
confidence: 99%
“…Occupancy models predicted overall stability of the population during the studied period (except in pinewoods), which roughly coincided with the population size stability showed under a typical climate change scenario (e.g., increasing temperature and decreasing rainfall, [ 14 ]). These results suggested some resilience to climate change that was in contradiction to expectations for a small endothermic species with African origin [ 46 ]: if white-toothed shrews were constrained by cold temperatures, it would be expected of climate warming to produce positive effects on their populations. However, positive effects of climate change were neutralized by the more relevant and negative effects of landscape change.…”
Section: Discussionmentioning
confidence: 72%